Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10633-015-9509-7
|View full text |Cite
|
Sign up to set email alerts
|

GUCY2D mutations in a Chinese cohort with autosomal dominant cone or cone–rod dystrophies

Abstract: The GUCY2D mutations were frequent in Chinese families with autosomal dominant cone or cone-rod dystrophies. All mutations were found in exon 13, which should be given priority during mutation screening analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Leber congenital amaurosis (LCA), the most severe form of IRD, appears as congenital or infantile‐onset vision loss caused by early onset rod and/or cone photoreceptor cell degeneration . Cone‐rod dystrophy (CRD) presents as a loss of central vision and/or peripheral vision . In addition to the extensive clinical overlap among IRDs, genetic overlap further complicates the molecular diagnosis of this group of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Leber congenital amaurosis (LCA), the most severe form of IRD, appears as congenital or infantile‐onset vision loss caused by early onset rod and/or cone photoreceptor cell degeneration . Cone‐rod dystrophy (CRD) presents as a loss of central vision and/or peripheral vision . In addition to the extensive clinical overlap among IRDs, genetic overlap further complicates the molecular diagnosis of this group of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous report of a Chinese cohort, Jiang et al reported nine unrelated probands with GUCY2D-RD ascertained from 74 probands with CORD (9/74, 12.2%) and seven of 15 ADCORD families had GUCY2D-RD (7/15, 46.7%). 37 The proportion of GUCY2D-RD in molecularly confirmed ADCORD was 34.6% in a UK cohort and 29.4% in a French cohort. 5,48 Given these results, the prevalence of GUCY2D-RD for CORD in Japan was not as high as that in other populations in Asia or Europe; however, GUCY2D-RD is a major cause of the ADCORD.…”
Section: Discussionmentioning
confidence: 87%
“… 11 13 , 16 , 56 These findings are consistent with previous reports of AD GUCY2D -CORD. 20 , 34 , 37 , 38 Therefore, comprehensive clinical investigations, including electrophysiological assessments, are essential for the diagnosis and monitoring of GUCY2D -RD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the review of previously published clinical data on GUCY2D , a MEDLINE/PubMed search was performed on 1 May 2020 (gucy2d eye, gucy2d dystrophy) and all publications with available clinical data have been included for further analysis (20 out of 112 publications) [ 11 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. For statistical analysis and creation of graphs, Graph Pad Prism 6 as well as R version 3.6.0 were used.…”
Section: Methodsmentioning
confidence: 99%